2013
DOI: 10.1002/oby.20287
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gross body fat‐water magnetic resonance imaging at 3 Tesla to dual‐energy X‐ray absorptiometry in obese women

Abstract: Improved understanding of how depot-specific adipose tissue mass predisposes to obesity-related comorbidities could yield new insights into the pathogenesis and treatment of obesity as well as metabolic benefits of weight loss. We hypothesized that three-dimensional contiguous “fat-water” MR imaging (FWMRI) covering the majority of a whole-body field of view (FOV) acquired at 3 Tesla (3T) and coupled with automated segmentation and quantification of amount, type and distribution of adipose and lean soft tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 41 publications
5
29
0
1
Order By: Relevance
“…17,18 Since BMI doesn't distinguish between fat tissue and lean muscle mass, it could be a poor marker of the kind of weight excess that causes cardiovascular risk. Direct measures of body fat are preferable, with computed tomography and magnetic resonance imaging volume measurements being the current gold standards, closely followed by dual-energy X-ray absorptiometry, 26 but these methods are costly and impractical. Other biometric indexes have sought to characterize body composition and fat distribution better than BMI.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Since BMI doesn't distinguish between fat tissue and lean muscle mass, it could be a poor marker of the kind of weight excess that causes cardiovascular risk. Direct measures of body fat are preferable, with computed tomography and magnetic resonance imaging volume measurements being the current gold standards, closely followed by dual-energy X-ray absorptiometry, 26 but these methods are costly and impractical. Other biometric indexes have sought to characterize body composition and fat distribution better than BMI.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that DEXA whole body scans are as reliable as whole body continuous MRI for measurement of total fat, total lean, trunk fat and trunk lean masses (39). The present study extends our prior findings by showing that estimating VAT directly from DEXA whole body scans is a more robust indicator of cardiometabolic risk in women with Class I and II obesity of European American and African American descent than other more commonly acquired anthropometric (weight, BMI, waist circumference, waist-hip ratio, waist-height ratio) and DEXA-derived surrogate measures of intra-abdominal adipose tissue (percent body fat, percent trunk fat, percent android fat, android/gynoid ratio).…”
Section: Discussionmentioning
confidence: 99%
“…Before each acquisition, the scanner was phantom calibrated according to manufacturer instructions. Duplicate scans after repositioning 12 subjects showed coefficients of variation <2% for fat and lean total and trunk masses (39). Scans were imported into an updated version of the software (version 13.6) and reanalyzed using algorithms that provided automatic segmentation of VAT from total abdominal fat within the android region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coefficients of variation from repeated measures of 12 randomly selected subjects were 0.58% for fat mass, 0.42% for lean mass, 1.35% for trunk fat and 1.02% for trunk lean [28]. …”
Section: Methodsmentioning
confidence: 99%